Improved diagnostic accuracy of combined anterior cruciate ligament/fibular collateral ligament injuries utilizing a simple physical exam measure - DePhillipo, Nicholas N.; LaPrade, Robert F. (Annals of Joint; Vol 4 (April 2019): Annals of Joint, 2019)
Diagnosing injuries to the posterolateral corner are often challenging for the clinician, especially in the acute setting (1). Physical examination and imaging such as magnetic resonance imaging (MRI) has led to improved diagnostic strategies and treatments for anterior cruciate ligament (ACL) injuries. However, in the event of concomitant ACL and fibular collateral ligament (FCL) injuries, FCL injuries may be missed or go undiagnosed due to lack of diagnostic sensitivity with MRI and potential for patient guarding during the clinical exam. This is particularly important in combined ACL and FCL injured patients, because unaddressed FCL tears have been shown to increase force on the ACL reconstruction graft (2). Therefore, identifying common injury patterns that may help increase the diagnostic accuracy of such combined injuries is warranted.